Characterization and functional inferences of a genome-wide DNA methylation profile in the loin () muscle of swine - Woonsu Kim (Asian-Australasian Journal of Animal Sciences, 2018)
Objective DNA methylation plays a major role in regulating the expression of genes related to traits of economic interest (e.g., weight gain) in livestock animals. This study characterized and investigated the functional inferences of genome-wide DNA methylome in the loin (longissimus dorsi) muscle (LDM) of swine. Methods A total of 8.99 Gb methylated DNA immunoprecipitation sequence data were obtained from LDM samples of eight Duroc pigs (four pairs of littermates). The reference pig genome was annotated with 78.5% of the raw reads. A total of 33,506 putative methylated regions (PMR) were identified from methylated regions that overlapped at least two samples. Results Of these, only 3.1% were commonly observed in all eight samples. DNA methylation patterns between two littermates were as diverse as between unrelated individuals (p = 0.47), indicating that maternal genetic effects have little influence on the variation in DNA methylation of porcine LDM. The highest density of PMR was observed on chromosome 10. A major proportion (47.7%) of PMR was present in the repeat regions, followed by introns (21.5%). The highest conservation of PMR was found in CpG islands (12.1%). These results show an important role for DNA methylation in species- and tissue-specific regulation of gene expression. PMR were also significantly related to muscular cell development, cell-cell communication, cellular integrity and transport, and nutrient metabolism. Conclusion This study indicated the biased distribution and functional role of DNA methylation in gene expression of porcine LDM. DNA methylation was related to cell development, cell-cell communication, cellular integrity and transport, and nutrient metabolism (e.g., insulin signaling pathways). Nutritional and environmental management may have a significant impact on the variation in DNA methylation of porcine LDM.